2017
DOI: 10.1002/mds.27043
|View full text |Cite
|
Sign up to set email alerts
|

Tonic and phasic changes in anteromedial globus pallidus activity in Tourette syndrome

Abstract: The results demonstrate the involvement of the associative/limbic pathway in the underlying pathophysiology of Tourette syndrome and point to tonic and phasic modulations of basal ganglia output as a key mechanisms underlying the abnormal state of the disorder and the expression of individual tics, respectively. © 2017 International Parkinson and Movement Disorder Society.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 35 publications
0
6
0
1
Order By: Relevance
“…Electrophysiology. Eight awake TS patients undergoing DBS electrode implantation had recordings of individual cells of the external and internal globus pallidus (GP) ( Israelashvili et al ., 2017). Some cells in each division of the GP showed transient changes in firing rates associated with tics.…”
Section: Resultsmentioning
confidence: 99%
“…Electrophysiology. Eight awake TS patients undergoing DBS electrode implantation had recordings of individual cells of the external and internal globus pallidus (GP) ( Israelashvili et al ., 2017). Some cells in each division of the GP showed transient changes in firing rates associated with tics.…”
Section: Resultsmentioning
confidence: 99%
“…The prior studies reviewed have focused on the GPi but have not explored the GPe as a potentially effective DBS target for TS treatment. A recent study examined tonic and phasic neuronal activities in the anterior GPe and GPi in 8 awake patients with TS while DBS electrodes were implanted [66]. The results showed that the expression of tics was accompanied by tonic and phasic changes of neuronal activity throughout the GP.…”
Section: Globus Pallidusmentioning
confidence: 99%
“…Es erfolgte eine Aktivitätsmessung der Neurone des GPi mit simultaner EMG-Ableitung. Es konnten Tic-bezogene neuronale Aktivierungen sowie Pausen tonisch aktiver inhibitorischer Interneurone festgestellt werden [30].…”
Section: Basalganglien Und Kortiko-striato-thalamokortikale Regelkreiseunclassified